The Relationship of Socio-Economic Status to Emotional and Consumptive Behavior - Hermawan, Eric (International Journal of Psychology and Health Science, 2023)
The Literature Review article on the Relationship of Socioeconomic Status to Emotional and Consumptive Behavior is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this study are: 1) Socioeconomic Status is related to Emotional; 2) Socioeconomic status relates to consumptive behavior; and 3) Emotional related to Consumptive Behavior. Apart from the exogenous variables that influence the endogenous variables, there are other influencing factors including: Environment, Friends and Association.